Memory and Identity in the Learned World Community Formation in the Early Modern World of Learning and Science - Scholten, Koen; van Miert, Dirk; Enenkel, Karl A.E (Intersections, 2022)
Accounts and analyses of the formation of scholarly and scientific communities in the early modern period by means of memory and collective identity.